IDENTIFICATION OF RISKS OF TIGER SHRIMP FARMING USING FAILURE MODE AND EFFECT ANALYSIS (FMEA) IN BELAWAN SICANANG VILLAGE - Lumbantobing, Surya Sevi Wijayanna; Zainal, Zainal (Institute of Computer Science (IOCS), 2024)
Black Tiger Shrimp breeding is has been done as the hereditary of the farm shrimp Belawan Sicanang urban village which has no uncertainty. The aims of the research to identify the sources of black tiger shrimp breeding and recommend the alternative strategy to overcome the problems. The method which used in the research is survey method with descriptive and Failure Mode and Effect Analysis (FMEA) methods. The result of the research shows that risk source of black tiger shrimp breeding are disease, high rainfall, the quality of seeds, quality of water, pest attack, the broke embankment, the selling price decreased, the land rent increased, the fertilizer price increased, the demand decreased, the saponin price increased, the fish seed increased and the dolomite price increased. The alternative strategy to overcome the risk is the application the Best Management Practice (BMP) dan konsep biosecurity principles. Upper drainage system, frying time, insertion / replacement of water in ponds, use of filters in water intake pipes, certified fry hatcheries, catching pests and repairing embankments.